1997
DOI: 10.1037/0022-0167.44.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Women's career development: Can theoretically derived variables predict persistence in engineering majors?

Abstract: Factors related to persistence in engineering, particularly for women, were examined in 278 upper level undergraduate women and men who, as entering students, enrolled in the college of engineering at a large midwestem university. An overall model of persistence was created by integrating constructs derived from a number of theories relevant to women's career behavior, including self-efficacy theory, expectancy-valence theory, interest congruence theory, and influences on women's career development. Hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
4
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 43 publications
12
145
4
3
Order By: Relevance
“…Students with high self-efficacy tend to perform better academically than students with low self-efficacy. Researchers have also reported that mathematics and science self-efficacy are significantly related to students' persistence in engineering 10,11 . Moreover, numerous studies have suggested that individuals' self-efficacy is related to their career-related and academic choices 12,13 .…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with high self-efficacy tend to perform better academically than students with low self-efficacy. Researchers have also reported that mathematics and science self-efficacy are significantly related to students' persistence in engineering 10,11 . Moreover, numerous studies have suggested that individuals' self-efficacy is related to their career-related and academic choices 12,13 .…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Women who pursued careers in mathematics, sciences, and technology consistently reported that the messages sent to them about capabilities in these male-dominated fields served as crucial sources of their self-efficacy 21 , a finding echoed in interviews conducted by Hutchison et al 15 with second-year engineering students. Other researchers have shown more generally that being encouraged by peers and faculty makes students more likely to put forth effort and persevere in their majors 4,11,15 .…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Studies by Jun (2005) and Herrera (2006) have provided a comprehensive overview of theoretical models that describe student continuation and dropout rates in both distance education institutions and institutions attended in person. Levin and Wyckoff (1991), House (1993), Schaeffers, Epperson, and Nauta (1997), BeserfieldSacre et al (1997), RiCharde (1998), French, Immekus, andOakes (2005) have all used logistic regression models to study student persistence in colleges.…”
Section: Neural Networkmentioning
confidence: 99%
“…Efficacy is based on a level of achievement and the strength of one's belief that the desired level of achievement can be attained [Pajares, 1996]. High selfefficacy in undergraduate STEM students has been linked to persistence (Lent et al, 2003;Margolis & Fisher, 2002;Besterfield-Sacre, Atman & Shuman, 1997) achievement (BesterfieldSacre et al, 1997Lent et al, 2003;Lent, Brown & Larkin, 1987;Schaefer, Epperson & Nauta, 1997) and interest (Hacket, Betz, Casas & Rocha-Singh, 1992;Lent et al, 2003;Lent et al, 1987;Lent, Lopez & Bieschke, 1991).…”
Section: Introductionmentioning
confidence: 99%